Biomarkers for Optimization and Personalization of Anti-TNFs in Pediatric Inflammatory Bowel Disease - Sara Salvador-Martín; Alejandra Melgarejo-Ortuño; Luis A. López-Fernández (MDPI AG, 2021)
The use of biological drugs has improved outcomes in pediatric inflammatory bowel disease (IBD). Prediction of the response to biological drugs would be extremely useful in IBD, and even more so in children, who are still growing physically and psychologically. Specific clinical, biochemical, and genetic parameters are considered predictive of response to biological drugs, although few studies have been carried out in children with IBD. In this review, we present current evidence on biological treatments used in pediatric IBD and the available biomarkers of response. We examine demographics, clinical characteristics, biomarkers (genetic, genomic, and cellular), and microbiota.